Bahasa Inggris - Luthfiana Nurtamara; Noorhidayati Noorhidayati; Sri Amintarti (Jurnal Penelitian Pendidikan IPA, 2023)
The Merdeka curriculum implemented in Indonesian schools allows teachers to create, select and modify teaching modules according to the context and needs of the learners. This research was used to develop a biology teaching module by exploring the potential of plants biodiversity in South Kalimantan, especially exotic fruit plants using the syntax of STEM-Project Based Learning model. The biology teaching module development design was used the ADDIE model (Analysis, Design, Development, Implementation and Evaluation).The results of the development in the form of teaching modules that have three sub-topics namely 1) levels of biodiversity (genes, species, and ecosystems); 2) species diversity of exotic fruit flora of South Kalimantan and 3) Biodiversity conservation efforts. The Teaching Module has complete components consisting of general information, core components and attachments. Validity and feasibility tests involved 3 experts (biology teachers with more than 5 years of teaching experience) and 10 students from SMAN 7 Banjarmasin. Data analysis was done descriptively from validity and feasibility test data. The results showed that the developed product is feasible to use in the learning process of biodiversity of E phase students in class X with excellent and very valid categories